Anti-PD-1 sintilimab-induced bilateral optic neuropathy in non-small cell lung cancer: A case report and literature review - Wang, Jian; Xiao, Xiaoyue; Dong, Xiaorong; Wu, Gang; Wang, Xinghua; Zhang, Ruiguang (Frontiers in Oncology, 2022)
Anti-PD-1/PD-L1 immunotherapy reactivates T-cell activity to boost the antitumor effect and may trigger autoimmune toxicity in various organ systems involving eyeball and periocular structures at the same time. The rarity of ocular immune-related adverse events should not prevent us from paying attention to this issue because of the bad consequences of visual impairment. This is the first case report of Anti-PD-1 sintilimab induced bilateral optic neuropathy in a 76-year-old man with squamous non-small cell lung cancer (NSCLC). The patient presented with sudden vision blurring without pain in both eyes after three therapeutic cycles of sintilimab plus chemotherapy. Based on the ophthalmic examination, laboratory and radiological results, our patient was diagnosed with optic neuropathy complication secondary to anti-PD-1 sintilimab treatment. Consequently, sintilimab was held and systemic steroids were administered. The follow-up review showed that the vision recovered and the size of the primary tumor continued to decrease with the response assessment as the partial response. In conclusion, this case report suggested that patients with NSCLC undergoing the treatment of anti-PD-1/PD-L1 therapy should be closely monitored for ophthalmic assessment and alert to the occurrence of sintilimab-induced optic neuropathy.